Patterns, Trends and Policy Processes in Spanish Secondary Education: Multiple Streams in a Multilevel Context - Eliseo López Sánchez; Esther del Campo (Central European Public Administration Review)
Educational policies in Spain have been characterized by conflict and continuous changes to legislation in the Central State. However, Spain is a decentralized State and the Autonomous Communities (regions) are responsible for implementing secondary education. The article aims at explaining and analyzing how Autonomous Communities have defined their educational models and policies for secondary education based on an unstable state legal framework. The analysis focuses on key elements of State legislation, such as the management methods of schools and the adaptation of policies to social differences between autonomous communities. Based on Zahariadis' multiple streams model, the article concludes by pointing out the importance of the context and its impact on the policies, the relevance of the ruling party's ideology in each Autonomous Community and the involvement of stakeholders in the implementation of secondary education policy.